Understanding Leadership Level of Principals, a Phenomenological Study in Punjab - Ghaffar, Rabia; Khan, Ayaz Muhammad (Annals of Human and Social Sciences, 2024)
The current study attempts to understand the leadership level of college principals in Punjab, Pakistan. Academia is facing various challenges. The need for vibrant, active, and proactive leadership is one of them. Leadership literature has a new dimension in the form of five levels of leadership by John Maxwell. There is a population and an empirical gap in the literature on the topic. It was a mixed-method research. A sequential explanatory design was used. The first was a survey, and in the second phase, the phenomenological approach was used to complete the study. Results revealed that demographics like experience and personal job status cause significant differences when assessing the principal's leadership level. College faculty believed their principals were at Pinnacle. It is recommended that this phenomenon be investigated at various levels of education and in different cultural contexts.